Influence of shallow hydrothermal fluid release on the functioning of phytoplankton communities - Tilliette, Chloé; Gazeau, Frédéric; Portlock, Gemma; Benavides, Mar; Bonnet, Sophie; Guigue, Catherine; Leblond, Nathalie; Lory, Caroline; Marie, Dominique; Montanes, Maryline; Pulido-Villena, Elvira; Sarthou, Géraldine; et al. (Frontiers in Marine Science, 2023)
In the Western Tropical South Pacific (WTSP) Ocean, a hotspot of dinitrogen fixation has been identified. The survival of diazotrophs depends, among others, on the availability of dissolved iron (DFe) largely originating, as recently revealed, from shallow hydrothermal sources located along the Tonga-Kermadec arc that fertilize the Lau Basin with this element. On the opposite, these fluids, released directly close to the photic layer, can introduce numerous trace metals at concentrations that can be toxic to surface communities. Here, we performed an innovative 9-day experiment in 300 L reactors onboard the TONGA expedition, to examine the effects of hydrothermal fluids on natural plankton communities in the WTSP Ocean. Different volumes of fluids were mixed with non-hydrothermally influenced surface waters (mixing ratio from 0 to 14.5%) and the response of the communities was studied by monitoring numerous stocks and fluxes (phytoplankton biomass, community composition, net community production, N2 fixation, thiol production, organic carbon and metal concentrations in exported material). Despite an initial toxic effect of hydrothermal fluids on phytoplankton communities, these inputs led to higher net community production and N2 fixation rates, as well as elevated export of organic matter relative to control. This fertilizing effect was achieved through detoxification of the environment, rich in potentially toxic elements (e.g., Cu, Cd, Hg), likely by resistant Synechococcus ecotypes able to produce strong binding ligands, especially thiols (thioacetamide-like and glutathione-like compounds). The striking increase of thiols quickly after fluid addition likely detoxified the environment, rendering it more favorable for phytoplankton growth. Indeed, phytoplankton groups stressed by the addition of fluids were then able to recover important growth rates, probably favored by the supply of numerous fertilizing trace metals (notably Fe) from hydrothermal fluids and new nitrogen provided by N2 fixation. These experimental results are in good agreement with in-situ observations, proving the causal link between the supply of hydrothermal fluids emitted at shallow depth into the surface layer and the intense biological productivity largely supported by diazotrophs in the WTSP Ocean. This study highlights the importance of considering shallow hydrothermal systems for a better understanding of the biological carbon pump.